The "Henrique Preto" Samba - Nascimento, Haydee; Tracey, Andrew (International Library of African Music, 1982)
Henrique Preto was a black, son of slaves, born in Santana de Parnaiba, and a cook by trade. He died at the age of 85 on the 1st of April, 1973, but still everyone in the city speaks about him, and even the children who did not know him refer to him with admiration. He is the most remembered figure on this night of the Parade of Fantasmas. The music of the parade is called the Samba of Henrique Preto. What you see in the dance performed in the streets is not properly speaking a samba. The rhythm is samba, but it is a crowd of people dancing as they like, shaking their arms, body and legs in a samba-like step and following the beat given by the music.
Keywords: African Music